Research On English Learning Strategies Based On Task-Based Language Teaching Method– A Case Study Of Chinese And Kyrgyzstan Students Using Mobile Games To Promote Language Learning (Architecture Image Studies, 2025)
Based on the pedagogical concept of task-based language learning, this study uses the technological products that students commonly use as auxiliary tools for task-based teaching, in order to study their enhancement effects on second language learning (using English learning as an example). This study implemented a quasi-experimental pretest and posttest design to investigate whether a mobile game-based second language learning strategy can improve high school students’ learning motivation and achievement. Selecting a suitable game and adding appropriate content for game-based English learning were the 2 key considerations for achieving the teaching goal. The experimental group comprised 38 students, whereas the control group comprised 40 students. The experimental period was 8 weeks. Through statistical methods, the results verified the positive effectiveness of a mobile game-based learning strategy for promoting high school students’ second language learning, consisting of motivation and achievement improvement. Conversely, this study found that the effectiveness of the mobile game-based learning strategy was not significant for students who did not like to play games. Finally, several findings and suggestions were proposed for future applications.